2003
DOI: 10.1080/02724990244000287
|View full text |Cite
|
Sign up to set email alerts
|

More is not necessarily better: Examining the nature of the temporal reference memory component in timing

Abstract: Three experiments compared the timing performance of humans on a modified temporal generalization task with 1, 3, or 5 presentations of the standard duration. In all three experiments subjects received presentations of a standard duration at the beginning of a trial block and then had to judge whether each of a number of comparison stimuli was or was not the standard. The duration of the standard changed between blocks. The three experiments varied the experimental design (between or within subjects), task dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 39 publications
10
100
0
Order By: Relevance
“…At the end of the timed interval, the switch opens, cutting the flow, and the number of accumulated pulses forms the basis for time perception. The accumulated counts may be compared with previously encoded durations to provide the basis for judgment and action (for recent discussions, see Jones & Wearden, 2003;Ogden & Jones, 2009;Ogden, Wearden & Jones, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the timed interval, the switch opens, cutting the flow, and the number of accumulated pulses forms the basis for time perception. The accumulated counts may be compared with previously encoded durations to provide the basis for judgment and action (for recent discussions, see Jones & Wearden, 2003;Ogden & Jones, 2009;Ogden, Wearden & Jones, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This point also suggests an important difference to put forward between temporal discrimination tasks and other classical timing tasks. Indeed, Jones and Wearden (2003) showed that varying the number of presentations of an anchor duration (one, three, or five times) did not improve temporal discrimination performance in a temporal generalisation task. However, temporal feedback quickly increases performance in quantification tasks.…”
Section: The Effect Of Task Duration Knowledge On Time Perceptionmentioning
confidence: 99%
“…However, this component has been understudied in the last few decades, as compared to other components or properties of timing models (e.g., the role of attention in the pacemaker-counter device). Nevertheless, some studies have focused on various aspects of temporal memory for time, such as the lifespan of memory traces (Gamache & Grondin, 2010); the interference between different temporal traces (Grondin, 2005) or between other task demands and memory traces (Ogden, Wearden, & Jones, 2008); the development of temporal memory (Rattat & Droit-Volet, 2005a, b, 2007; the effect of the number of presentations of a standard duration on temporal discrimination (Jones & Wearden, 2003); the influence of pharmacological substances on temporal memory (Meck, 1983); or the electroencephalographic basis of memory traces (Ng, Tobin, & Penney, 2011).…”
Section: Abstract Time Perception Memory Attentionmentioning
confidence: 99%
“…In a bisection task, transferring into memory the accumulation of a given interval would involve a multiplicative storage constant, K * , whose variability is normally distributed (L. A. Jones & Wearden, 2003). Variance in such a task may also be associated with the distribution in reference memory of each of the short (S) and the long (L) intervals to be learned (Penney, Gibbon, & Meck, 2000).…”
Section: A Neuroscientific Approachmentioning
confidence: 99%